198 Policy maker's perceptions of the role of research in injury prevention legislation. (1st September 2016) - Macpherson, A; Rothman, L; Fuselli, Pamela; Belton, Kathy; Olsen, Lise; Pike, Ian
Abstract : Background: Injury prevention policy is crucial for the safety of Canada's children; however, legislation is not adopted uniformly across the country. Researchers and policy makers must work together to develop effective legislation that is evidence-based but little is known regarding policy makers views regarding the importance of research in facilitating the legislative process. Methods: Purposive snowball sampling identified individuals involved in injury prevention practice and policy throughout Canada. In an online survey, respondents identified injury topics relevant to them and rated the importance of enablers to injury legislation using a 5 point Likert scale. Results: There were 57 respondents with representation from all 10 provinces. The most common topics were, bicycle helmets (77%), cell phone-distracted driving (63%), booster seats (49%), ski helmets (42%), and graduated driver's licensing (37%). The most frequently identified enabler was that research/surveillance was readily available (59%). Other commonly reported research enablers were: research of sufficient quality/quantity that was easy to understand and in a useful format and affiliation of researchers with reputable organisations. Less important was researchers having similar priorities as policy makers and understanding the policy process. The importance of different research enablers varied by injury topic. Conclusions: Although policy makers identified the importance that injury prevention research was readily available, it appeared to be less important that researchers had similar priorities or understood the policy process, with variability by topic. This presents a challenge for researchers to conduct timely research and emphasises the need for ongoing relationships with policy makers with discussions early in the research process. This would facilitate the development of common injury prevention priorities to ensure research is used effectively in the legislative process.